The employees perception of ISO Implementation in Administration Department at Universiti Malaysia Sabah (UMS) / Dona Bondly U Yakim - Bondly U Yakim, Dona (2010)
The International Organization for Standardization or known as ISO is an international-standard-setting body composed of representatives from various national standards organizations which main objective is to promote the development of standardization to be applied in an organization. By having ISO, every organization can increase their productivity and gain customer loyalty towards their company because the customer may trust and satisfied with their product and service and therefore, tend to be loyal. In this research, it will aim to know whether the organization that has received the ISO certificate has any impact to the employees’ job performance which is this research conducted specific in the administration department at University Malaysia Sabah (UMS). There are three main objectives in this research which is firstly to study whether years of employment can influence the understanding on the ISO concept. Secondly, to compare the understanding of ISO concept between gender and thirdly, to study whether the understanding on the ISO concept influence the employee’s commitment towards the ISO implementation.